Japan : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This Report reviews the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Japan. The assessment reveals that Japan has made good progress in bringing its regime for AML/CFT into compliance with international standards. A comprehensive legal and institutional framework is in place, and Japan has achieved a good level of compliance with the FATF 40+8 Recommendations. However, some weakness is noted in the area of international cooperation, and the supervision of AML/CFT compliance for postal banks.